A Magma Accretion Model for the Formation of Oceanic Lithosphere: Implications for Global Heat Loss - Valiya M. Hamza; Roberto R. Cardoso; Carlos H. Alexandrino (International Journal of Geophysics)
A magma accretion model of oceanic lithosphere is proposed and its implications for understanding its thermal field examined. The new model (designated Variable Basal Accretion—VBA) assumes existence of lateral variations in magma accretion rates and temperatures at the boundary zone between the lithosphere and the asthenosphere. However, unlike the previous thermal models of the lithosphere, the ratio of advection to conduction heat transfer is considered a space dependent variable. The results of VBA model simulations reveal that the thickness of the young lithosphere increases with distance from the ridge axis, at rates faster than those predicted by Half-Space Cooling models. Another noteworthy feature of the new model is its ability to account for the main features in the thermal behavior of oceanic lithosphere. The improved fits to bathymetry have been achieved for the entire age range and without the need to invoke the ad-hoc hypothesis of large-scale hydrothermal circulation. Also, use of VBA model does not lead to artificial discontinuities in the temperature field of the lithosphere, as is the case with GDH (Global Depth Heat Flow) reference models. The results suggest that estimates of global heat loss need to be downsized by at least 25%.